Strain‐Modulated Ferromagnetism at an Intrinsic van der Waals Heterojunction - Fujita, Ryuji; Gurung, Gautam; Mawass, Mohamad‐Assaad; Smekhova, Alevtina; Kronast, Florian; Toh, Alexander Kang‐Jun; Soumyanarayanan, Anjan; Ho, Pin; Singh, Angadjit; Heppell, Emily; Backes, Dirk; Maccherozzi, Francesco; et al. (Advanced functional materials, 2024)
The van der Waals interaction enables atomically thin layers of exfoliated 2D materials to be interfaced in heterostructures with relaxed epitaxy conditions, however, the ability to exfoliate and freely stack layers without any strain or structural modification is by no means ubiquitous. In this work, the piezoelectricity of the exfoliated van der Waals piezoelectric α‐In2Se3 is utilized to modify the magnetic properties of exfoliated Fe3GeTe2, a van der Waals ferromagnet, resulting in increased domain wall density, reductions in the transition temperature ranging from 5 to 20 K, and an increase in the magnetic coercivity. Structural modifications at the atomic level are corroborated by a comparison to a graphite/α‐In2Se3 heterostructure, for which a decrease in the Tuinstra‐Koenig ratio is found. Magnetostrictive ferromagnetic domains are also observed, which may contribute to the enhanced magnetic coercivity. Density functional theory calculations and atomistic spin dynamic simulations show that the Fe3GeTe2 layer is compressively strained by 0.4%, reducing the exchange stiffness and magnetic anisotropy. The incorporation of α‐In2Se3 may be a general strategy to electrostatically strain interfaces within the paradigm of hexagonal boron nitride‐encapsulated heterostructures, for which the atomic flatness is both an intrinsic property and paramount requirement for 2D van der Waals heterojunctions. This study focuses on the captivating interplay between the ferromagnetic Fe3GeTe2 and the piezoelectric α‐In2Se3, both 2D van der Waals (vdW) materials. Strained heterojunctions exhibit several compelling transformations: increased domain density, reduced Curie temperature, and emergent magnetostrictive ferromagnetic domains. Using α‐In2Se3 is a versatile approach to strain‐tune vdW materials, including graphite and Te based vdW chalcogenides.